“Estrategias lúdicas para el fortalecimiento del proceso de enseñanza-aprendizaje en las nociones básicas de la multiplicación en el cuarto año de educación general básica de la unidad educativa sagrado corazón de Jesús fe y alegría, patricia pilar, 2024-2025”. - Estrada Chacha, Jeniffer Cecilia (2025)
The objective of this research was to strengthen the teaching-learning process of multiplication tables through playful strategies. The goal was to foster dynamic and practical learning, which contributed to a stronger understanding of mathematical concepts. Traditional multiplication teaching, centered on memorization of multiplication tables, presented limitations due to its mechanical approach, which did not promote logical thinking or student motivation. Lack of interest in the subject, combined with non-interactive teaching methods, hindered the acquisition of meaningful knowledge, resulting in poor academic performance in mathematics. Various research studies have shown that implementing playful activities increased students' motivation and enthusiasm, which facilitated both retention and understanding of the multiplication tables. However, it was found that, despite teachers' adoption of playful strategies, their application was limited and lacked the necessary structure to generate a real impact on learning. Furthermore, a lack of guidance and motivation from teachers prevented these activities from reaching their full potential.